2017
DOI: 10.1111/jcmm.13216
|View full text |Cite
|
Sign up to set email alerts
|

The EF‐1α promoter maintains high‐level transgene expression from episomal vectors in transfected CHO‐K1 cells

Abstract: In our previous study, we demonstrated that episomal vectors based on the characteristic sequence of matrix attachment regions (MARs) and containing the cytomegalovirus (CMV) promoter allow transgenes to be maintained episomally in Chinese hamster ovary (CHO) cells. However, the transgene expression was unstable and the number of copies was low. In this study, we focused on enhancers, various promoters and promoter variants that could improve the transgene expression stability, expression magnitude (level) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…The activity of promoters with predicted ‘ubiquitous’ expression, such as the four studied here, will still depend greatly on the lineage of the host cell (32). However, EF-1 promoter was found to be active and resistant to silencing in cells where other viral promoters may become silenced (33). Therefore, future work will be required to determine if the superior performance of EF-1 and CMV in expressing long RNA sequences can be extrapolated to other cell primary cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of promoters with predicted ‘ubiquitous’ expression, such as the four studied here, will still depend greatly on the lineage of the host cell (32). However, EF-1 promoter was found to be active and resistant to silencing in cells where other viral promoters may become silenced (33). Therefore, future work will be required to determine if the superior performance of EF-1 and CMV in expressing long RNA sequences can be extrapolated to other cell primary cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized sequences replaced the CMV promoter (i.e. the CMV promoter was excised and replaced with CMV promoter mutants) in the previously described pEM vector (Figure 1 (a)) [21], and they were named as mutant-404 and mutant-542 ( Figure 1(b)). By contrast, the EF-1α and CAG promoters were generated using polymerase chain reaction (PCR).…”
Section: Vector Constructionmentioning
confidence: 99%
“…In our previous study, we investigated enhancers, various promoters and promoter variants on transgene expression in CHO-K1 cells and found that the EF-1a promoter is a potent regulatory sequence for episomal vectors and maintains high transgene expression [21]. However, only the CHO-K1 cell line, which was unfit for gene therapy owing to its differences from human cells, was tested.…”
Section: Introductionmentioning
confidence: 99%
“…More general promoters such as CMV (cytomegalovirus) 54 , 58 , 60 , 62 and EFS (elongation factor-1 alpha short) 5 , 65 can be used to express the CRISPR in multiple tissues, including muscle, retina, heart, and lung, for simultaneous gene editing of various tissues in mice. Compared with the CMV promoter, the elongation factor-1 alpha (EF1a) promoter tends to give more consistent and prolonged expression regardless of cell type or physiology 91 , 92 . EF1a is more stable in long-term culture because it maintains high transgene expression and stability and the copy number of episomal vectors 91 .…”
Section: Aav-crispr-based In Vivo Genome Editing Imentioning
confidence: 99%